Co-processing of the arrowroot-chitosan by spray drying - Yudi Wicaksono; Yuli Witono; Herlina .; Nuri . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
Starch is one of the most widely used excipient in the manufacture of solid dosage forms. One of few problems associated with starch is its poor flowability so can’t used as excipient in direct compression tablet. The purpose of these studies was to develop of the arrowroot starch for use as excipient in direct compression tablet. The arrowroot starch was co-processing with chitosan by spray drying. The suspension of arrowroot starch-chitosan for feed in spray drying were prepared with three different ratios (1:1, 2:1 and 3:1). The product of co-processing were evaluated for morphology, moisture content, viscosity, angle of repose, flow rate of granules, bulk density, tapped density and Carr’s index. Results showed that co-process excipient of arrowroot starch-chitosan have spherical in shape, moisture content in the range of 4.70–5.10 % w/w, viscosity in the range of 1.77-2.17 mPas, angle of repose was found to be < 380, flow rate of granules in the range of 1,5 – 4,0 g/s, bulk density in the range of 0.47-0.59 g/mL, tapped density in the range of 0.59–0.79 g/mL l and Carr’s index in the range of 19.03-25.08 %.Key words: arrowroot starch, co-process excipient, direct compression